Scheduling manufacturing system with sequence dependent setup and maintenance - Hendra Teja Wirawan (2015)
Few researches in scheduling literature have considered setup and maintenance concurrently. This thesis analyzes sequence-dependent setup scheduling problem with non-resumable case of maintenance consideration to minimize makespan (maximizing utilization) on a single machine. Some parts of machine time are required for setup and maintenance activity, and in this study it is assumed that these two can be performed simultaneously. The analysis is divided into three parts, based on its job arrival and maintenance period assumption. Algorithms with dynamic job arrival assumption are tested on historical data of an actual semiconductor testing facility system. It is observed that the proposed algorithms are able to improve machine productive utilization by up to ~6% and average WIP by up to --40%.